Polymerase chain reaction-based discrimination of viable from non-viable Mycoplasma gallisepticum - Tan, Ching Giap; Ideris, Aini; Omar, Abdul Rahman; Chen, Pei Yii; Kleven, Stanley H. (Agricultural Research Council, 2014)
The present study was based on the reverse transcription polymerase chain reaction (RT-PCR) of the 16S ribosomal nucleic acid (rRNA) of Mycoplasma for detection of viable Mycoplasma gallisepticum. To determine the stability of M. gallisepticum 16S rRNA in vitro, three inactivation methods were used and the suspensions were stored at different temperatures. The 16S rRNA of M. gallisepticum was detected up to approximately 20–25 h at 37 °C, 22–25 h at 16 °C, and 23–27 h at 4 °C. The test, therefore, could detect viable or recently dead M. gallisepticum (< 20 h). The RT-PCR method was applied during an in vivo study of drug efficacy under experimental conditions, where commercial broiler-breeder eggs were inoculated with M. gallisepticum into the yolk. Hatched chicks that had been inoculated in ovo were treated with Macrolide 1. The method was then applied in a flock of day 0 chicks with naturally acquired vertical transmission of M. gallisepticum, treated with Macrolide 2. Swabs of the respiratory tract were obtained for PCR and RT-PCR evaluations to determine the viability of M. gallisepticum. This study proved that the combination of both PCR and RT-PCR enables detection and differentiation of viable from non-viable M. gallisepticum.